The Effectiveness of Diversion in Resolving Juvenile Breast Groping Cases - Shanty, Fiorentina Elfrida; Rasdi, Rasdi (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Sexual harassment committed by minors, particularly in the form of breast-grabbing, is a complex phenomenon due to the offender’s ongoing psychosocial development. The legal handling of such cases requires not only a repressive approach but also the application of restorative justice through diversion mechanisms. This study aims to analyze the effectiveness of diversion in resolving a breast-grabbing case committed by a minor in Semarang. This research uses a juridical-empirical method with a qualitative approach, focusing on a case study at the Class I Correctional Center (Bapas) in Semarang. Data were collected through interviews and the analysis of legal documents related to the diversion process. The findings indicate that the diversion was conducted in accordance with legal provisions and resulted in an agreement involving an apology, financial compensation, and a commitment to rehabilitate the offender. However, the study also identifies limitations in the victim’s recovery and the continuity of the offender’s rehabilitation. It further questions whether justice is truly achieved when the victim remains psychologically affected, and highlights the risk of behavioral normalization if rehabilitation is not effectively implemented. Therefore, the effectiveness of diversion in sexual offense cases should be understood not only from a procedural standpoint but also in terms of achieving substantive justice for all parties involved.